OPTIMALISASI KECERDASAN SPIRITAUL MELALUI PEMBELAJARAN BTQ - M. Nauval Hadad Fanani; Rahmad Salahuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In a dynamic and complex modern society, maintaining inner balance and tranquility increasingly depends on spiritual intelligence. Islamic education, particularly through the study of the Qur'an and Hadith (BTQ), plays a vital role in fostering this intelligence, aiding individuals in overcoming challenges and building strong moral character. This study aims to explore the relationship between learning motivation and spiritual intelligence in the BTQ learning process at SMA Telkom Sidoarjo. Using a qualitative methodology, the primary data sources were students, teachers, and the principal. Data collection methods included in-depth interviews recorded verbatim, field notes from observations, and documentation of students' assignments. Observations were made to assess the school's initiatives in nurturing students' spiritual intelligence. The findings revealed that effective BTQ learning involves a deep understanding of sacred texts and the practical application of their values in daily life. Indicators of students' spiritual intelligence were measured through their understanding of the Qur'an and Hadith, self-reflection, worship practices, participation in religious activities, ethics, and moral behavior, as well as their ability to face challenges positively and appreciate spiritual values. The research highlights the importance of innovative teaching strategies and the integration of technology to enhance spiritual intelligence. Triangulation of data from various sources ensured the validity of the findings. This study is expected to contribute to the development of a more effective BTQ curriculum and teaching methods at SMA Telkom Sidoarjo, promoting spiritual growth among students.